Pengaruh Kesehatan Kerja dan Keselamatan Kerja Terhadap Produktivitas Karyawan Pada PT Haleyora Powerindo Bandung - Dindin Bernhardin; Ridwan Syahril Ismail (Jurnal Ekonomi Manajemen Perbankan, 2020)
This study aims to analyze the effect of occupational health and safety on employee productivity at PT. Haletora Powerindo. The sampling technique in this study uses a nonprobability sampling technique with saturated sampling method that is 75 employees. Analysis and testing of hypotheses used are multiple linear regression methods with research instruments using a questionnaire.The results showed that the occupational health program partially affected the work productivity of employees at PT Haleyora Powerindo. The work safety program partially affects the work productivity of employees at PT Haleyora Powerindo. Occupational health and work safety programs simultaneously affect the work productivity of employees at PT Haleyora Powerindo.